1996
DOI: 10.1037/0278-7393.22.4.896
|View full text |Cite
|
Sign up to set email alerts
|

Time-course analysis of semantic and orthographic context effects in picture naming.

Abstract: In Experiment 1, the authors used a picture–word task to investigate the time courses of semantic interference, orthographic facilitation, and their interaction. Five stimulus onset asynchronies (SOAs), from −200 ms (word first) to 200 ms, in steps of 100 ms were used. The results showed that the semantic interference effect was restricted to a small SOA range around zero, that the orthographic facilitation effect almost spanned the whole SOA range used, and finally, that the two effects modified each other. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

35
392
4

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 254 publications
(431 citation statements)
references
References 95 publications
(240 reference statements)
35
392
4
Order By: Relevance
“…Using this design, we can investigate whether there is a temporal overlap in the processing of the words in a sentence and a flow of information between them, just as there is a temporal overlap between the processing of the target and distracter words in a picture-word interference paradigm and a flow of information between them. Consistent with previous studies conducted using the picture-word interference paradigm (e.g., Damian et al, 2001;Lupker, 1979;Starreveld & LaHeij, 1996), in the current study we demonstrated both semantic interference effects and phonological facilitation effects. Thus, in Experiments 1 and 2, semantic interference effects were repeatedly observed between lemmas in both same phrase and different phrase sentences.…”
Section: Discussionsupporting
confidence: 92%
“…Using this design, we can investigate whether there is a temporal overlap in the processing of the words in a sentence and a flow of information between them, just as there is a temporal overlap between the processing of the target and distracter words in a picture-word interference paradigm and a flow of information between them. Consistent with previous studies conducted using the picture-word interference paradigm (e.g., Damian et al, 2001;Lupker, 1979;Starreveld & LaHeij, 1996), in the current study we demonstrated both semantic interference effects and phonological facilitation effects. Thus, in Experiments 1 and 2, semantic interference effects were repeatedly observed between lemmas in both same phrase and different phrase sentences.…”
Section: Discussionsupporting
confidence: 92%
“…els of spoken word production (e.g., Abdel Rahman & Melinger, 2009, Damian & Martin, 1999, Levelt et al, 1999, Roelofs, 1992, 2003, 2007, 2008a, 2008b, Schriefers et al, 1990, Starreveld & La Heij, 1996.…”
Section: The Locus Of the Semantic Interference Effectmentioning
confidence: 99%
“…The relation the distractor word bears with the picture name (e.g., semantic, phonological, etc.) is manipulated and effects obtained are thought to inform researchers about processes involved in word production.One specific effect has long been assumed to provide evidence about the nature of lexical selection: semantic interference (e.g., Damian & Martin, 1999;Levelt, Roelofs, & Meyer, 1999;Roelofs, 1992;Schriefers, Meyer, & Levelt, 1990;Starreveld & La Heij, 1996). This effect concerns the finding that response times (RTs) are longer for picture naming when the distractor is from the same semantic category as the picture (pictured cat, word dog) relative to unrelated distractors (pictured cat, word pen).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…During the early processes of conceptual encoding and lexical selection, several closely related lexical concepts and the corresponding names may become simultaneously activated (e.g., when an object could either be called a sofa or couch), and the speaker must then select the most appropriate item amongst those that are active. Several models of lexical access propose that the process of lexical selection is competitive, such that the selection of a target is hindered by coactivation of competitors (e.g., Abdel Rahman and Melinger, 2009;Bloem and La Heij, 2003;Howard et al, 2006;Levelt et al, 1999;Piai et al, 2014;Roelofs, 1992Roelofs, , 2003Starreveld and La Heij, 1996). In other models, lexical selection is not seen to be a competitive process: A target is selected as soon as it has reached a threshold of activation regardless of the activation levels of other lexical items (see Finkbeiner and Caramazza, 2006;Mahon et al, 2007).…”
Section: Introductionmentioning
confidence: 99%